Undermined Syncretism - Om Prakash (International Institute of Islamic Thought, 2011)
The syncretic cultural tradition of India for the last five thousand years is a noble legacy and a contribution of India to the world. Some major religions of the world took their birth in India. The incoming of foreigners added new elements to India’s cultural tradition, and enriched it—and subsequently, this tradition evolved into a composite culture. This paper primarily looks into the aspect of what happened during the colonial period in India, which undermined this rich syncretic tradition and subsequently fragmented the Indian subcontinent along the religious lines. The paper is based upon the hypothesis that separatism is a gradual process, which is nurtured during a period of time and which leads to the eruption of division, partition, or the breaking up of the state. The result of this process becomes a strong movement if actions to combat it are not launched. This paper also explores how Muslim separatism was fed by various reactionary elements, which included colonial and imperial forces comprised of members of different castes, creeds, and religions.